Effects of Conditioned Pain Modulation on the Nociceptive Flexion Reflex in Healthy People: A Systematic Review. Issue 9 (September 2019) - Dhondt, Evy; Van Oosterwijck, Sophie; Coppieters, Iris; Danneels, Lieven; Van Oosterwijck, Jessica
Abstract : Objectives: The nociceptive flexion reflex (NFR) is a spinal reflex induced by painful stimuli resulting in a withdrawal response. Research has shown that the NFR is inhibited through endogenous pain inhibitory mechanisms, which can be assessed by conditioned pain modulation (CPM) paradigms. Although accumulating research suggests that the NFR can be affected by CPM, no clear overview of the current evidence exists. Therefore, the present review aimed at providing such a synthesis of the literature. In addition, the influence of personal factors on the CPM of the NFR was investigated. Materials and Methods: A systematic review was performed and reported following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Five electronic databases were searched to identify relevant articles. Retrieved articles were screened on eligibility using predefined inclusion criteria. Risk of bias was investigated according to the modified Newcastle-Ottawa Scale. Levels of evidence and strength of conclusion were assigned following the guidelines of the Dutch Institute for Healthcare Improvement. Results: Forty articles were included. There is some evidence that CPM produced by thermal or mechanical stimuli induces inhibitory effects on the NFR. However, inconclusive evidence exists with regard to the effect of electrical conditioning stimuli. While several personal factors do not affect CPM of the NFR, increased cognitive interference is associated with reduced NFR inhibition. Discussion: The present review demonstrates that certain types of nociceptive conditioning stimuli have the potential to depress, at the spinal level, nociceptive stimuli elicited from distant body regions. Although CPM of the NFR seems to be robust to the influence of several personal factors, it can be affected by cognitive influences. Abstract : Supplemental Digital Content is available in the text.